A framework for priority-setting in climate smart agriculture research. (November 2018) - Thornton, Philip K.; Whitbread, Anthony; Baedeker, Tobias; Cairns, Jill; Claessens, Lieven; Baethgen, Walter; Bunn, Christian; Friedmann, Michael; Giller, Ken E.; Herrero, Mario; Howden, Mark; Kilcline, Kevin; et al.
Abstract: Climate-smart agriculture (CSA) is widely promoted as an approach for reorienting agricultural development under the realities of climate change. Prioritising research-for-development activities is crucial, given the need to utilise scarce resources as effectively as possible. However, no framework exists for assessing and comparing different CSA research investments. Several aspects make it challenging to prioritise CSA research, including its multi-dimensional nature (productivity, adaptation and mitigation), the uncertainty surrounding many climate impacts, and the scale and temporal dependencies that may affect the benefits and costs of CSA adoption. Here we propose a framework for prioritising agricultural research investments across scales and review different approaches to setting priorities among agricultural research projects. Many priority-setting case studies address the short- to medium-term and at relatively local scales. We suggest that a mix of actions that span spatial and temporal time scales is needed to be adaptive to a changing climate, address immediate problems and create enabling conditions for enduring change. Highlights: Prioritising CSA research activities is challenging, primarily because it is multi-dimensional. We propose and illustrate a simple six-element framework as a "map" to guide prioritisation. Most priority setting activities need a mix of different quantitative and qualitative methods. This mix needs to address actions that span spatial and temporal time scales to ensure CSA research effectiveness.